Macroeconomic Impact of Foreign Exchange Intervention : Some Cross-country Empirical Findings - Jin, Zhongxia; Wang, Haobin; Zhao, Yue. (Washington, D.C. : International Monetary Fund, 2021)
Based on VAR analyses across 26 countries, we show that, although foreign exchange intervention (FXI) is effective in stabilizing the nominal exchange rate in the short run, its impacts on the real exchange rate are less significant: Limitations on nominal exchange rate flexibility may induce adjustments to the real exchange rate through domestic prices. We find that countries that intervene more heavily in response to external shocks experience greater general and asset price volatility, which is not conducive to countering the impact of external shocks. We show that China's macroeconomic responses to external shocks are broadly consistent with international experiences among intervening countries. The simple methodological framework adopted in this paper is meant to examine a broad set of macroeconomic variables and bears limitations; our findings serve to motivate more structural analysis on FXI's macroeconomic impacts going forward.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Foreign Exchange; Inflation; Informal Economy; Price Level; Underground Econom